Peran Guru Dalam Mengembangkan Rasa Percaya Diri Anak Melalui Metode Bernyanyi Dengan Gerakan - Apriani, Apriani; Sari, Henni Maya; Pebriani, Ela (Jurnal Multidisiplin, 2025)
The purpose of this study was to describe the role of teachers in developing children's self-confidence through the singing method with movements in group B at Lembayung Indah Kindergarten, Bengkulu City. This research is a qualitative research. Data were collected using interviews and documentation. The subject of this research is the role of teachers in developing children's self-confidence through the singing method with movements at Lembayung Indah Kindergarten, Bengkulu City. Data analysis was carried out by collecting data, agreeing data, and drawing conclusions. Data reduction is the process of determining, focusing, simplifying, and transforming data. While the presentation of data is a depiction of all information about how the presentation of data here is limited as a set of information that gives the possibility of drawing conclusions and taking action. The results of interviews obtained on the role of the teacher in developing self-confidence in children through the method of singing with movement found 3 Intovert children, 5 Extrovert children and 7 Ambivert children. The conclusion in this study is that there is an influence of the teacher's role in developing children's self-confidence through the method of singing with movement.